Effect of the ember element in increasing the efficiency of liquefied petroleum gas stoves - Sudarno Sudarno (Institut za istrazivanja i projektovanja u privredi, 2021)
The purpose of this study was to determine the effect of use ember element from woven nickel wire to increasing the efficiency of the LPG stoves. It is supposed that high-temperature embers can burn more fuel around the wire, thereby increasing the area of complete combustion. The test was conducted by means of a Water Boiling Test (WBT) and the number of ember layers varied from one to four. It was found that the use of elements of fire without reflectors could increase efficiency by 8.32%, with the highest efficiency being with the use of a single layer ember element of the fire, of 61.71%. However, the use of elements of fire in the finned heat reflectors causes efficiency to decrease, as the pattern to put elements of fire interfere with the reflectivity. This means the heat reflection is blocked by the pattern and trapped between the reflector and pattern elements. As a result, the heat energy from the reflector reflection cannot be forwarded to the combustion zone. The test results also show that the temperature distribution from ember element use can increase the area of complete combustion.